Must God Be Dead? Reinventing the Sacred. Issue 3 (3rd July 2017) - Kauffman, Stuart
ABSTRACT: Newton became a death knell for a theistic God and for a non-epiphenominal mind. The culprit is the deterministic causal closure of classical physics. Two major revolutions are taking us beyond this closure. The first is Quantum Mechanics, which is non-deterministic. The second revolution may just be happening. The emergence and evolution of life in our or any biosphere is governed by no law at all. This freedom suggests one sense of God as the natural creativity of the Universe.